'Rise Like Lions After Slumber': Dissent, Protest and (Post-)Politics in Manchester. Issue 4 (1st October 2016) - Haughton, Graham; Gilchrist, Anna; Swyngedouw, Erik
Abstract: This article aims to improve our understanding of post-politicization by examining the role of 'ordinary' urban protest movements, using the example of a protest in Alexandra Park, an inner city park in Manchester, UK. The critical literature on postpolitics has improved our understanding of exceptional, large-scale protests, but we know much less about how smaller scale protests emerge and in time wind down. Our research is revealing of the post-politicizing tactics of the city authorities in containing protest and of how the protesters lost momentum, focusing on contesting techno-managerial processes for consultation and undertaking scientific surveys. Whilst universalizing claims were made about democratic enfranchisement, the authorities were able to counter and diffuse these.